Effects of IL-6 and TNF-α Cytokines on Cell Proliferation in Androgen Dependent/Independent Prostate Cancer Cell Lines - Serhad Onat; Feray Köçkar; Sümeyye Aydoğan Türkoğlu (Journal of Advanced Research in Natural and Applied Sciences)
Prostate cancer is the second most common types of cancer among men worldwide. Prostate cancer, caused by abnormal and uncontrolled growth of the cells that make up the prostate tissue, is second only to related deaths in men. Cytokines, which have a significant impact on the response of the immune system, play an active role in the development of prostate cancer. This study determined the effect of proinflammatory cytokines, IL-6 and TNF-α on the proliferation of prostate cancer (PCα) cell lines. MTT test was used for the effect of cytokines applied at different doses and hours on cell viability. According to our results, IL-6 cytokine caused a high increase in proliferation in androgen-dependent LNCaP cells, while androgen-independent PC-3 cells showed different proliferative effects in time and dose-dependent manner. TNF-α cytokine had a negative effect on the proliferation of androgen-dependent LNCaP cells, while it increased the proliferation level of androgen-independent PC-3 cells. These results show that the effects of cell lines-on the proliferation of cells are different depending on their androgen sensitivity, which will be used in different cytokinetic studies to determine the inflammatory response to treat prostate cancer. It is especially important to consider this condition during the advancement of prostate cancer treatment strategies.